IMPACT TESTING OF SMAW WELDING CONNECTIONS ON A36 STEEL WITH VARIATION OF WELDING CURRENT - Chris Jeremy Verian Sitorus; Alamsyah A; Uswah Pawara; Suardi S; Jusma Wahidah; Harlian Kustiwansa; Sri Leli Melenia; Cindy Lionita Agusty (Journal of Marine-Earth Science and Technology, 2025)
This study aims to determine the effect of SMAW welding joints on impact strength and to determine the effect of impact loads on the fracture structure of ASTM A36 steel material. This research is based on welding theory, steel and electrode material theory, and impact testing theory. The determining factor of this research is the amount of welding current used. There is an increase in absorbed energy and impact strength for each variation of current, but this increase is not constant. Where at a strong current of 125 A there is an increase in E of 4.35 Joules and HI by 0.054375 J/mm2 compared to a strong current of 100 A. However, at a strong current of 150 A there is only an increase in E of 0.1 Joules, while for an increase in the value of HI by 0.00125 J/mm2 compared to a current of 125 A.